Assessment of the thoracic aorta after aortic root replacement and/or ascending aortic surgery using 3D relaxation-enhanced angiography without contrast and triggering - Gietzen, Carsten; Janssen, Jan Paul; Tristram, Juliana; Cagman, Burak; Kaya, Kenan; Terzis, Robert; Gertz, Roman; Gietzen, Thorsten; Pennig, Henry; Bunck, Alexander C.; Maintz, David; Persigehl, Thorsten; et al. (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveRelaxation-Enhanced Angiography without Contrast and Triggering (REACT) is a novel 3D isotropic flow-independent non-contrast-enhanced MRA (non-CE-MRA) and has shown promising results in imaging of the thoracic aorta, primarily in patients without prior aortic surgery. The purpose of this study was to evaluate the performance of REACT after surgery of the aortic root and/or ascending aorta by performing an intraindividual comparison to CE-MRA.Material and methodsThis retrospective single center study included 58 MRI studies of 34 patients [mean age at first examination 45.64 ± 11.13 years, 31 (53.44%) female] after ascending aortic surgery. MRI was performed at 1.5T using REACT (ECG- and respiratory-triggering, Compressed SENSE factor 9, acquired spatial resolution 1.69 × 1.70 × 1.70 mm3) and untriggered 3D CE-MRA. Independently, two radiologists measured maximum and minimum vessel diameters (inner-edge) and evaluated image quality and motion artifacts on 5-point scales (5 = excellent) for the following levels: mid-graft, distal anastomosis, ascending aorta, aortic arch, and descending aorta. Additionally, readers evaluated MRAs for the presence of aortic dissection (AD) and graded the quality of depiction as well as their diagnostic confidence using 5-point scales (5 = excellent).ResultsVessel diameters were comparable between CE-MRA and REACT (total acquisition time: 05:42 ± 00:38 min) with good to excellent intersequence agreement (ICC = 0.86–0.96). At the distal anastomosis (minimum/maximum, p < .001/p = .002) and at the ascending aorta (minimum/maximum, p = .002/p = .06), CE-MRA yielded slightly larger diameters. Image quality for all levels combined was higher in REACT [median (IQR); 3.6 (3.2–3.93) vs. 3.9 (3.6–4.13), p = .002], with statistically significant differences at mid-graft [3.0 (2.5–3.63) vs. 4.0 (4.0–4.0), p < .001] and ascending aorta [3.25 (3.0–4.0) vs. 4.0 (3.5–4.0), p < .001]. Motion artifacts were more present in CE-MRA at all levels (p < .001). Using CE-MRA as the standard of reference, readers detected all 25 cases of residual AD [Stanford type A: 21 (84.0%); Stanford type B: 4 (16.0%)] in REACT with equal quality of depiction [4.0 (3.0–4.5) vs. 4.0 (3.0–4.0), p = .41] and diagnostic confidence [4.0 (3.0–4.0) vs. 4.0 (3.0–4.0), p = .81) in both sequences.ConclusionsThis study indicates the feasibility of REACT for assessment of the thoracic aorta after ascending aortic surgery and expands its clinical use for gadolinium-free MRA to these patients.